The impact of LNG offshore terminal on sea temperature and sea currents in the northern Adriatic Sea - JELIĆ MRČELIĆ, GORANA; JURIĆ, MAJDA; SUPIĆ, NASTJENJKA; DUTOUR SIKIRIĆ, MaMATHIEU thieu (Mediterranean Marine Science, 2023)
The aim of this paper is to simulate the impact of a potential offshore LNG terminal on sea temperature (in autumn and spring/ summer) and sea currents (in autumn/winter) at three different depths (at the sea surface, at 25 m depth and at the seabed) in the northern Adriatic Sea from 14 November 2015 to 06 August 2016 using the Regional Ocean Modelling System (ROMS) model. The location of the potential offshore LNG terminal Istria (in the northern Adriatic Sea) was selected using the visual PROMETHEE method. The potential LNG terminal uses seawater for LNG heating and the seawater cooled to a temperature of 9°C returns to the marine environment. Although the differences in sea temperature with and without the discharge fit within normal temperature ranges, the simulations show that the discharge changed the speed and direction of sea currents at the sea surface not only in the wider northern Adriatic, but in the entire Adriatic. This is probably due to the specific circulation in the Adriatic, where cold water affects the geostrophic balance, an important part of the circulation field that depends on density (a function of salinity and temperature). Atmospheric conditions in the broader vicinity of the LNG terminal would also be affected by redistribution of air-sea fluxes due to changes in surface temperature. Changes in circulation would alter environmental conditions by redistributing nutrients, oxygen, etc. Further multi-year simulations of changes in the circulation system are needed, but other physical parameters (density, salinity, river inflow...) should also be included in the simulations to determine the cumulative impact of a potential LNG terminal on the marine environment.